(untitled) (BIRDEM Medical Journal, 2025)
Background: Emphysematous pyelonephritis (EPN) is an uncommon, acute and severe necrotizing infection affecting the renal parenchyma, collecting system and surrounding tissues. This study was planned to describe the demographic, clinical, laboratory and imaging characteristics and in-hospital outcomes of patients with EPN. Methods: This retrospective study was done at BIRDEM General Hospital, Dhaka, Bangladesh between 2021 and 2023. Patients’ clinical, laboratory and imaging characteristics and in-hospital outcomes were recorded in case record forms at the time of discharge or death, if were any. Results: Total patients were 16 with female predominance (10, 62.5%). Mean age of patients was 57.1 (range 29 - 67) years. Risk factors for EPN were diabetes mellitus (16, 100%) and renal stones (3, 18.8%). Fever (16, 100%), loin pain (11, 68.8%), vomiting (10, 62.5%) and dysuria (10, 62.5%) were common presenting features. All (16, 100%) patients had leukocytosis and uncontrolled blood glucose (HbA1c >7%). Complications included acute kidney injury (AKI) (7, 43.8%), hyponatremia (5, 31.3%) and bacteremia (3, 18.8%). Escherichia coli (11, 68.8%) was the most common urinary isolate. Most patients (11, 68.8%) had class 2 EPN, 3 (18.8%) had class 3B and 1 (6.3%) had class 3A disease. One (6.3%) patient had class 4 EPN with emphysematous cystitis. Along with medical management, four (25%) patients required surgery (open drainage in 3, open drainage with double J stenting in 1). None required nephrectomy. Mean hospital stay was 8 (range 6 - 11) days and there was no death. Conclusion: EPN occurred predominantly among female diabetic patients with poor glycemic status, who presented with fever, loin pain, vomiting and dysuria. Two-fifths of patients had AKI and one-fourth required surgery. None required nephrectomy and there was no mortality. BIRDEM Med J 2025; 15(1): 5-8